Grit and Mindset Among College Students: How do they affect students in completing their thesis? - Resi Nurfauziah Rohim; Gian Sugiana Sugara; Muhammad Muhajirin; Eris Irawan (Edupotensia Foundation, 2025)
Final-year students face various challenges in the thesis preparation process, including problem identification, topic selection, data collection and analysis, seeking references, and difficulties with academic advisors. This study aims to examine the correlation between mindset and grit among final-year students at Universitas Muhammadiyah Tasikmalaya. Using a quantitative approach with a correlational design, this research investigates the relationship between mindset and grit. The sample consists of 206 out of 442 final-year students at Universitas Muhammadiyah Tasikmalaya, selected through random sampling. Data analysis employed the Pearson product-moment technique. Results indicate a positive correlation between grit and growth mindset (r = 0.514, p=0.001), while grit shows no correlation with a fixed mindset (r = -0.031, p = 0.657). These findings suggest that classical guidance services can enhance grit by fostering a growth mindset.